A rural medieval settlement in Roxburghshire: excavations at Springwood Park, Kelso 1985-6 - Dixon, Piers; Bateson, J D; Bown, L; Ford, B; Grove, D; Nye, S; Turner, J; Welfare, A; Wickham-Jones, C R (Proceedings of the Society of Antiquaries of Scotland, 1999)